The aspect of climate change in predicting energy demand in HVAC systems - Kwiecień, Dariusz (Instal, 2025)
One of the effects of observed and forecasted climate change is the change in energy demand in HVAC systems.  The article analyzed a number of available climate data for Warsaw (Okęcie), conventionally classified as historical, contemporary and prognostic. Based on the analysis of these data, climate change indicators were determined in the form of heating degree days (HDD), cooling degree days (CDD), humidification gram days (HGD) and dehumidification gram days (DGD). Significant differences were found in the values   of these indicators for different climate data. In the case of RCP (Representative Concentration Pathway) scenarios allowing for climate forecasts until 2100, a general downward trend in HDD and HGD rates and an increase in CDD and DGD rates was observed. In order to verify the values   of climate change indicators, the annual energy demand for heating, humidification, cooling and dehumidification of air in an exemplary air conditioning system was calculated. The obtained results indicate their general compliance with the calculated indicators. In addition, the time of failure to meet the assumed thermal and humidity conditions was determined for each of the cases using a conventional air conditioning system. Currently, depending on contemporary data, the time when these conditions are exceeded in a way that is unacceptable to users may constitute from 2.2% to approximately 5% of the total time of use of rooms during the year. However, in 2100, depending on the RCP scenario, this time may reach 5.9% for RCP 4.5 and as much as 10.8% for RCP 8.5. Therefore, these trends should be taken into account today in the design of new buildings and HVAC systems.
Keywords: climate change indicators; heating; cooling; humidification; dehumidification; indoor air condition